Czynniki warunkujące wybór kraju do lokowania bezpośrednich inwestycji zagranicznych - Stawicka, Magdalena (Factors Influencing the Choice of Country or FDI, 2007)
The foreign direct investments (FDI) is one of the main factors of favourable globalization of the economic life as well as one of the most visible effects of progressive world globalization. The main aim of this article is to present the most important factors influencing the choice of location for foreign direct investments. The analysis was conducted on a basis of accessible literature as well as on the results of the author's own research on the subject.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 44-54